2014
DOI: 10.1007/s11596-014-1371-4
|View full text |Cite
|
Sign up to set email alerts
|

Combined low-dose aspirin and warfarin anticoagulant therapy of postoperative atrial fibrillation following mechanical heart valve replacement

Abstract: The safety and efficacy of combined low dose aspirin and warfarin therapy in patients with atrial fibrillation after mechanical heart valve replacement were evaluated. A total of 1016 patients (620 females, mean age of 36.8±7.7 years) admitted for cardiac valve replacement and complicated with atrial fibrillation after surgery were randomly divided into study (warfarin plus 75-100 mg aspirin) or control (warfarin only) groups. International normalized ratio (INR) and prothrombin time were maintained at 1.8-2.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 29 publications
0
12
0
5
Order By: Relevance
“…Substantial evidence suggests that aspirin is an effective antithrombotic at 75–150 mg per day, with further increases amplifying the bleeding risk without protective benefit 40 . This may explain the discordance between these studies and others with more positive overall findings, which tended to use maximal doses of 100 mg per day 35,36 …”
Section: Antithrombotic Therapies In Mechanical Valve Replacementmentioning
confidence: 74%
See 4 more Smart Citations
“…Substantial evidence suggests that aspirin is an effective antithrombotic at 75–150 mg per day, with further increases amplifying the bleeding risk without protective benefit 40 . This may explain the discordance between these studies and others with more positive overall findings, which tended to use maximal doses of 100 mg per day 35,36 …”
Section: Antithrombotic Therapies In Mechanical Valve Replacementmentioning
confidence: 74%
“…Such studies have consistently found the addition of antiplatelets successfully reduced the incidence of thromboembolic events. [32][33][34][35][36][37] However, this is often at the price of increased bleeding risk, leading to ambiguity over whether there is truly a net benefit. [32][33][34]38 Where the risk of hemorrhage is increased by concomitant antiplatelet use, the increase is often predominantly due to minor bleeding events that pose no serious or long-term complications.…”
Section: Through Open Access T a B L E 1 Summary Of Guidelines For Inmentioning
confidence: 99%
See 3 more Smart Citations